Poverty in Nigeria: A Social Protection Framework for the Most Vulnerable Groups of Internally Displaced Persons - Okon, Emmanuel Okokondem (American International Journal of Social Science Research, 2018)
Despite strong economic growth in Nigeria, 54% of the population remains in poverty. Of significant concern is the fact that the poverty rate has doubled in the past 20 years. Internal displacement in Nigeria is a recurring and large-scale phenomenon and has affected most of the country’s 36 states. The country has seen many waves of displacement, both small and large scale, caused essentially by conflict, generalized violence, natural disasters and human rights violations all leading to loss of lives, properties and livelihood which in turn lead to deprivation, poverty and vulnerability. The operational definition of vulnerability in this paper as applied to the most vulnerable IDPs covers those categories of internally displaced persons who may never recover from the shocks of displacement and may become chronic poor as such worsening the poverty situation in Nigeria. This paper attempts a social protection framework for the most vulnerable IDPs as well as exit strategies. Protecting this vulnerable group is vital to poverty reduction especially as the country is presently suffering the adverse effects of dwindling revenue from crude oil and gas sectors, which today accounts for about 95 per cent of its revenue.